O conselho municipal de assistência social de São Paulo e o controle social da política pública: uma análise a partir do programa Criança Feliz - Campana, Fernanda (2024)
Introduction: The panorama of Social Assistance in Brazil reflects a constitutional commitment in constant evolution, facing historical challenges. The tutelary approach of the State generated obstacles, combated in the 80s, resulting in the transformation of Social Assistance from philanthropy to a right, evidenced by the Unified Social Assistance System in 2004. The 1988 Constitution institutionalized popular participation, establishing new guidelines, and decentralization consolidated the paradigm shift, recognizing social assistance as a right. Social Assistance Councils, representative and crucial, seek to balance diverse interests, promoting democratic participation. However, they face challenges such as precarious infrastructure, governmental influence, and lack of professionalization, compromising participatory management and the promotion of social rights. Studies also question the legitimacy of the Councils as effective spaces of social control of Public Policy. Faced with these questions, this dissertation will focus on the Municipal Social Assistance Council of São Paulo (COMAS). This choice is justified by the challenges faced by this entity, from its late formation in 2001 to recent issues, such as the analysis and approval of the Early Childhood Program - Child Happy in 2017. The mismatch between the initial decision of COMAS and the subsequent approval of the mentioned Program under new municipal management highlights persistent challenges in the legitimation process of the Council. Objective: Thus, the objective of the dissertation will be to analyze the challenges for the effectiveness of the Municipal Social Assistance Council of São Paulo as a legitimate space for social control of Public Policy, based on the experience of the Child Happy Program. Methodology: It is an exploratory study, qualitative in nature, based on literature review, document analysis, and unstructured interviews with former councilors and representatives of civil society and the public sector, whose mandates coincided with the assessment of the Child Happy Program. Civil society representatives, higher education professionals, are elected in a specific forum, forming the segment of Civil Society Organizations and are recognized in spaces of mobilization and social participation in public policies. The interviewed representative of the public sector is a higher education professional appointed to a position of trust in public management. Content analysis will be applied to the interview results. Results: The main results of this research highlight the challenges to the existence and legitimacy of Councils, such as: the ability to exist, problems relating to representation, conflict of interests, the responsibility of councilors as public agents, as well as possible solution mechanisms such as the proposed review of the Creation Law, the civil society electoral process and the appointment of public servants. The research serves as a lesson learned applicable not only to the specific context of São Paulo, but also as a significant contribution to strengthening the democratic and participatory management of public social assistance policy throughout the country.